Analysis of the Historical Literacy Movement for Class X Students at State Senior High Schools 1 Gunung Sugih - Wati, Kurnia Pradila; Setiawati, Elis; Setiawan, Johan; Suryani, Susi (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to determine and analyze (1) How is the historical literacy movement of class historical literacy of students at State Senior High Schools 1 Gunung Sugih. The method used in this research is a qualitative research method with a descriptive analysis approach. The subjects used in this research were literature, the deputy principal for academic affairs, history teachers, students in classes X.1 and X.2 as well as other sources that were relevant and supported this research. This research uses observation data collection techniques, questionnaires, interviews and documentation. The data techniques used are data reduction, data presentation, and drawing conclusions. The results of this research can be concluded (1) there are three stages in the historical literacy movement of class factors, namely supporting factors and inhibiting factors, (3) the school's efforts to increase students' historical literacy movement with support from the school community, teachers provide support or encouragement and motivation for historical literacy, teachers invite students to get to know historical sources, teachers use various interesting and creative learning strategies that support developing students' historical literacy in the historical literacy movement.